Morphology and phylogenetic relationships of fossil snake mackerels and cutlassfishes (Trichiuroidea) from the Eocene (Ypresian) London Clay Formation. (21st June 2018) - Beckett, Hermione T.; Giles, Sam; Johanson, Zerina; Friedman, Matt
Abstract: 'Gempylids' (snake mackerels) and trichiurids (cutlassfishes) are pelagic fishes characterized by slender to eel‐like bodies, deep‐sea predatory ecologies, and large fang‐like teeth. Several hypotheses of relationships between these groups have been proposed, but a consensus remains elusive. Fossils attributed to 'gempylids' and trichiurids consist almost exclusively of highly compressed body fossils and isolated teeth and otoliths. We use micro‐computed tomography to redescribe two three‐dimensional crania, historically assigned to † Eutrichiurides winkleri and † Progempylus edwardsi, as well as an isolated braincase (NHMUK PV OR 41318). All from the London Clay Formation (Eocene, Ypresian), these specimens represent some of the oldest fossils identified as trichiuroids. We find that † Eutrichiurides winkleri does not show diagnostic characters of † Eutrichiurides, and it is assigned to a new genus. To investigate the placement of these fossils relative to extant lineages, we combine existing morphological character sets for 'gempylids' and trichiurids along with published mitogenomic data. Our analyses recover a monophyletic Trichiuridae nested within a paraphyletic 'Gempylidae'. The taxon formerly known as † Eutrichiurides winkleri is considered Trichiuroidea incertae sedis, while † Progempylus edwardsi and NHMUK PV OR 41318 are recovered within the 'gempylid' grade. Using previously published descriptions and character optimizations from our phylogenetic analyses we suggest possible placements for laterally compressed body fossils assigned to Trichiuroidea († Argestichthys, † Abadzekhia, † Chelifichthys, † Anenchelum, † Eutrichiurides, † Musculopedunculus ).